The Effect of Different Types of Support for the Interactive Books Content on Cognitive Achievement of the Science Course for Second Grade Intermediate Female Student in Sabya Education Department - Namazi, Nawal Abdullah Qassem; Muakili, Khaled Hussein Khalwi (Journal of Curriculum and Teaching Methodology, 2022)
The aim of the current research is to reveal the effect of the different types of content support in interactive books (audio, visual, audiovisual) on the cognitive achievement in the science course for second-grade female students in the intermediate education department, and The research followed the descriptive and quasi-experimental approaches; Where the research sample consisted of (90) female students from the second grade average who were chosen and distributed randomly into three experimental groups, the first group was presented with a visual pattern, while the audio pattern was used for the second group, and the third group was used for the audio-visual pattern The research tool was the achievement test, There is a significant impact of the content of interactive books on the cognitive achievement in the science course for second-grade students in the Department of Education for a Boy, regardless of the patterns of content support used in it, in addition to the presence of a statistically significant difference at the level of significance (0.05) between the average scores of the students in the pre and post measurements of the research groups. The three in the cognitive achievement test are due to the main effect of the content support styles (audio, visual, audiovisual), these differences came in favor of the audio-visual content support style compared to the audio style, and the research recommended the need to employ content support styles in interactive books in teaching science.
Keywords: interactive books; Content support patterns; cognitive achievement